Low health literacy in older patients with uncontrolled blood pressure at secondary care - Renata Romanholi Pinhati; Paula Liziero Tavares; Elisa de Oliveira Marsicano; Neimar da Silva Fernandes; Fernando Antonio Basile Colugnati; Marcus Gomes Bastos; Rogério Baumgratz de Paula; Helady Sanders Pinheiro (HU Revista, 2019)
Background: Low health literacy (LHL) is common among patients with chronic diseases. Studies on the association between LHL and uncontrolled blood pressure are limited to primary and tertiary levels of healthcare. Objective: We evaluated the prevalence and association between LHL and uncontrolled blood pressure in hypertensive patients in a secondary healthcare in Brazil. Material and methods: Our study had a cross-sectional design and included 485 patients, between August/2014 to March/2016. We evaluated health literacy, by Short Assessment of Health Literacy for Portuguese-Speaking Adults (SAHLPA-18), and the blood pressure control. Individuals with a score ≤14 in SAHLPA-18 were considered as LHL, and individuals with blood pressure ≥140/90 (or ≥130/80 in diabetic patients) were considered as having uncontrolled blood pressure. Results: A total of 56.0% female, with mean age 62.0±12.6 years. Illiterate participants were 61.6%, and 65.4% earned up to one reference wage. Both uncontrolled blood pressure and LHL were highly prevalent (75.1% and 70.9%, respectively), but there was no association between these two parameters. In multivariate analysis, uncontrolled blood pressure was associated with age (OR:0.96, CI:0.94-0.98, p<0.001), diabetes mellitus (OR:4.36, CI:2.54-7.51; p<0.001) and number of pills (OR:1.16, CI:1.08-1.25, p<0.001). Conclusion: Even we found a high prevalence of LHL, the lack of association between LHL and uncontrolled blood pressure may be due to demographic characteristics of the sample, i.e., elderly people with low income and low schooling. HL assessment provides important information that supports actions to improve hypertension control and treatment.